The Impact of Applying Management by Objectives on Employee Performance: An Applied Study on Employees in Charitable Organizations in Al-Ahsa (International Journal of Financial, Administrative and Economic Sciences, 2026)
This study sought to investigate the influence of applying the Management by Objectives (MBO) approach on employee performance within charitable organizations located in Al-Ahsa Governorate. The importance of this research arises from its attempt to explore how implementing MBO practices can enhance the effectiveness and efficiency of employees working in charitable associations across the Kingdom of Saudi Arabia. To achieve this purpose, the study adopted a descriptive–analytical methodology, as it provides an appropriate framework for describing the phenomenon under investigation and analyzing the relationships among its variables.The research population comprised stakeholders and decision-makers occupying various managerial levels—including general managers, department heads, branch managers, and section supervisors—as well as other employees working in the charitable associations under study in Al-Ahsa. A simple random sampling technique was employed to reach the respondents by distributing structured questionnaires. Out of 300 questionnaires distributed, 293 were returned, and 283 were found valid for statistical analysis. The data were processed and analyzed using a set of statistical methods through the Statistical Package for the Social Sciences (SPSS).The findings revealed a statistically significant relationship between the Management by Objectives approach and employee performance in charitable associations in Al-Ahsa Governorate. The dimensions that showed a significant impact included trust between supervisors and subordinates, participation in goal setting, employees’ commitment to achieving goals, and continuous feedback. These results were significant at the (α ≤ 0.05) level.Based on these findings, the study recommended maintaining the application of the MBO approach as a key managerial tool for evaluating and improving employee performance. It further emphasized the importance of strengthening mutual trust between supervisors and subordinates, involving all staff in determining the organization’s goals, reinforcing employee commitment, and ensuring that managers provide regular feedback regarding progress toward achieving those goals.
Keywords: Management by Objectives; Employee Performance; Charitable Organizations in Al-Ahsa Governorate